Strategic management plan for Aboitiz One - Platon, Gypsyjoy B. Cuevas (Animo Repository, 2001)
Aboitiz One, Inc. operates within the Package Delivery Service Industry. Package delivery service industry is composed of firms that handle pickup and delivery of packages, be it in the form of documents, cash or cargoes. The industry satisfies the need of individuals, corporations and even governments for fast and safe delivery service. Analysis of the changes in the macro-economic environment which comprise the social, economic, political, technological and institutional environments has brought about opportunities and threats to the industry to which the Company may exploit or protect itself. The opportunity available to the industry is the Retail Trade Act of 2000. On the other hand, the threats facing the industry are: (1) High inflation rates and economic slowdown (2) Foreign bank liberalization (3) Approval of Electronic Commerce Act (4) Growing users of internet on Full Open Sky Policy and the Philippines becoming a hub for foreign players . Internal analysis of the Company reveals the following strengths and weaknesses: Strengths: (1) On-line facility for customers inquiry (2) Selection of selling channels (3) Procurement through Bayantrade (4) Maintenance of own aircraft. Weaknesses: (1) Poor accounts receivable and billing system (2) No system to aid information on competitor analysis or benchmarking (3)Lack of research and development programs to equip itself to global competition (3) Lack of coordination among business units (4) Inadequate training programs for frontlines and customer service group (5) Delivery service delays. The strategies were formulated based on the opportunities and threats facing the industry, the Company's strengths and weaknesses, the personal values of the decision makers and societal expectations. (1) Expand operations in the worldwide market by forming an alliance with foreign/global players so the Company can increase the width of its product line, expand its customer segment and its geographic market served. (2) Expand the degree to which the Company seeks technological leadership. (3) Improve the degree to which the Company provides ancillary services with its product lines. (3) Increase the extent to which the Company seeks low cost position. The Company has the following competitive advantages: (1) E-Trace, which allows customers to inquire the status of its packages or cargoes online.(3) Numerous and strategically located outlets, which allows customers to easily locate and avail the Company's services.